Effectiveness of Law Enforcement on Narcotics Crimes through Synchronization of Authority Between the National Narcotics Agency (BNN) and the Indonesian National Police - Hepni, Aswari (Al-Adalah: Jurnal Hukum dan Politik Islam, 2025)
Drug trafficking in Indonesia is a serious issue that requires special attention from the government and law enforcement officials. Efforts to eradicate drugs are carried out by the National Police of the Republic of Indonesia and the National Narcotics Agency, which collaborates with relevant agencies within the country and with international institutions. This article discusses the synchronization of authority between Â National Narcotics Agency and Indonesian National Police in investigating narcotics crimes. This research uses normative legal methods with a conceptual and statutory approach. Synchronizing the investigation of narcotics crimes between the BNN and the National Police from the perspective of legal certainty in Indonesia is a strategy that aims to increase the effectiveness of law enforcement for narcotics crimes, while reducing the potential for conflict between the National Police and the BNN